Evaluation of HOMER modeling and simulation for three microgrid cases - Wu, Zhenyu (2017)
With the increasing consciousness for sustainable development and energy efficiency, microgrids have been gaining much more attention in recent years. Before a microgrid is established, simulation of the microgrid system is necessary and of great importance. HOMER Pro is one of the simulation software packages especially used for the microgrid and its working is based on simulation, optimization and sensitivity analysis. So the main objectives of this project are to introduce the software HOMER Pro. Use this software to simulate three different microgrid cases and analyze the simulation results. Firstly, a microgrid is introduced. Then the software HOMER Pro is introduced in detail, especially the principles of cost calculation and optimization. Next, the first test cast, Pulau Ubin Microgrid, is modelled and analyzed. And the second test case, CleanTech One Hybrid AC/DC Microgrid, is modelled and analyzed. Furthermore, the third test case, Future Smart Building Hybrid Grid, is scheduled, modelled, and analyzed. The simulation results of all these three cases are clear and reasonable. And Homer PRO is proven to be a great microgrid simulation software. Besides, this project also made a good preparation for future research.